2019
DOI: 10.3390/pharmacy7030102
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions in Norway: A Systematic Review

Abstract: Prescription medicines aim to relieve patients’ suffering but they can be associated with adverse side effects or adverse drug reactions (ADRs). ADRs are an important cause of hospital admissions and a financial burden on healthcare systems across the globe. There is little integrative and collective knowledge on ADR reporting and monitoring in the Norwegian healthcare system. Accordingly, this systematic review aims to investigate the current trends in ADR reporting, monitoring, and handling in the Norwegian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Adverse drug reactions (ADRs) pose a substantial and growing burden on healthcare systems and are the leading cause of hospital readmissions and associated co-morbidities, many of which can be prevented. 1,2 Cutaneous adverse drug reactions (CADRs) are the most frequent adverse events resulting from medication use. 3 CADRs encompass all adverse events related to drug eruption, regardless of aetiology.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…Adverse drug reactions (ADRs) pose a substantial and growing burden on healthcare systems and are the leading cause of hospital readmissions and associated co-morbidities, many of which can be prevented. 1,2 Cutaneous adverse drug reactions (CADRs) are the most frequent adverse events resulting from medication use. 3 CADRs encompass all adverse events related to drug eruption, regardless of aetiology.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…Other causes for ADR risks might be elderly patients' contact with multiple prescribers, lack of time among GPs, clinical guidelines' for a single-disease focus, and knowledge limitations [8]. A recent systematic review in Norway also found ADRs to be fairly common, and the authors reported a lack of necessary feedback and quality improvement systems [9]. Several lists of potentially inappropriate drugs (PIDs) in the elderly and harmful drug combinations have been established [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…LTV acts as an inhibitor of the HCMV DNA terminase complex by interacting with the pUL56 subunit of such complex and preventing the cleavage of concatemeric DNA into monomeric genome length DNA, which ultimately inhibits DNA packaging into the virion. LVT displays good efficacy against different clinical isolates of HCMV, including GCV-resistant strains, and is ineffective against all other herpesviruses [217].…”
Section: Treatmentmentioning
confidence: 99%